Theory of Digital Automata - Borowik, Bohdan; Karpinskyy, Mykola; Lahno, Valery; Petrov, Oleksandr; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
This book serves a dual purpose: firstly to combine the treatment of circuits and digital electronics, and secondly, to establish a strong connection with the contemporary world of digital systems. The need for this approach arises from the observation that introducing digital electronics through a course in traditional circuit analysis is fast becoming obsolete. Our world has gone digital. Automata theory helps with the design of digital circuits such as parts of computers, telephone systems and control systems. A complete perspective is emphasized, because even the most elegant computer architecture will not function without adequate supporting circuits. The focus is on explaining the real-world implementation of complete digital systems. In doing so, the reader is prepared to immediately begin design and implementation work. This work serves as a bridge to take readers from the theoretical world to the everyday design world where solutions must be complete to be successful.
1 Digital and Analog Quantities -- 2 Number Systems, Operations, and Codes -- 3 Binary Arithmetic -- 4 Error Correction in Digital Systems -- 5 Boolean Algebra -- 6 Basic Logical Functions and Gates. Logic Design -- 7 Minimizing Boolean Functions -- 8 Latches, Flip-Flops, Counters, Registers, Timer, Multiplexer, Decoder, Etc -- 9 Machines Moore and Mealy -- Appendices -- Glossary -- References -- Subject Index.
Keywords: Engineering; Logic design; Information theory; Electronic circuits; Engineering; Circuits and Systems; Logic Design; Information and Communication, Circuits; Electronic books